Nitrogen and potassium deficiency effect on growth and basal stem rot disease severity of oil palm seedlings planted on peat soil - Abdul Wahab, Nur Syuhada (2015)
Palm oil is the most commonly used vegetable oil, with around 45.3 million tons produced annually worldwide, it has many uses in several products including cosmetics, cleaning products, and also processed food. However, oil palm plantations in Malaysia have many disease problems, which cause the reduction of oil palm yield. The main diseases that often attack oil palm tree is basal stem rot (BSR), which is caused by the fungi called Ganoderma boninense. Diseased oil palm tree cannot survive long and cause the decrease in oil palm yield. Therefore, the objective of this study was to determine the effect of deficiency of nitrogen (N) and potassium (K) on the (i) growth and (ii) disease severity of oil palm seedlings infected by Ganoderma boninense planted on peat soil. The experiment was conducted in a randomized complete block design (RCBD) with six blocks (3 blocks inoculated with Ganoderma boninense, 3 blocks not inoculated with Ganoderma boninense) with each block having five replications. The treatments used were (i) deficiency, (ii) optimum, and (iii) control. The quantity of fertilizer differentiated by the deficiency (treatment 1), optimum (treatment 2), and control (treatment 3). The parameter measured included seedling height, bole diameter, number of fronds per seedling, disease severity, photosynthesis rate and relative chlorophyll content. The result obtained from this study showed that optimum (treatment 2) shows a very good growth compared to the other treatments although it was inoculated by Ganoderma boninense and the disease severity index was also lower compared to other treatments.